2010
DOI: 10.1016/j.brainres.2009.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variance contributes to dopamine and opioid receptor antagonist-induced inhibition of intralipid (fat) intake in inbred and outbred mouse strains

Abstract: Preference for and intake of solid and emulsified fat (Intralipid) solutions vary across different mouse strains. Fat intake in rodents is inhibited by dopamine and opioid receptor antagonists, but any variation in these responses as a function of genetic background is unknown. Therefore, the present study compared the ability of dopamine D1-like (SCH23390) and general opioid (naltrexone) receptor antagonism to alter intake of fat emulsions (Intralipid) in mice. Two-h intakes of 5% Intralipid were measured (5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
4
14
0
Order By: Relevance
“…Furthermore, we have also demonstrated that fat ingestion can activate pro-opiomelanocortin (POMC) neurons in the hypothalamus, which synthesize beta-endorphin (5). Many reports have suggested that administration of opioid receptor antagonists can attenuate fat preference, an observation that is consistent with our findings (4,(6)(7)(8).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, we have also demonstrated that fat ingestion can activate pro-opiomelanocortin (POMC) neurons in the hypothalamus, which synthesize beta-endorphin (5). Many reports have suggested that administration of opioid receptor antagonists can attenuate fat preference, an observation that is consistent with our findings (4,(6)(7)(8).…”
supporting
confidence: 82%
“…Furthermore, we have also demonstrated that fat ingestion can activate pro-opiomelanocortin (POMC) neurons in the hypothalamus, which synthesize beta-endorphin (5). Many reports have suggested that administration of opioid receptor antagonists can attenuate fat preference, an observation that is consistent with our findings (4,(6)(7)(8).A significant amount of experimental evidence implicates the opioid system in the reward and reinforcement of drug addiction. We previously demonstrated that, similar to drug administration, fat ingestion can serve as a reinforcer by inducing place preference or strong lever-pressing behavior in mice (we define these as "reinforcing effects") (9, 10).…”
supporting
confidence: 80%
“…Our laboratory found that marked strain differences occurred in the reduction of sucrose intake following NTX over a wide dose range (0.01-5 mg/kg) in eleven inbred strains (Dym et al, 2007), and following the DA D1 antagonist, SCH23390 (SCH), but not the DA D2 antagonist, raclopride, over a wide dose range (50-1600 nmol/kg) in eight inbred strains (Dym et al, 2009). Correspondingly, marked strain differences occurred in the reduction of fat (Intralipid) following NTX and SCH in 8 inbred strains (Dym et al, 2010). In addition to the intrinsic palatability of sugars, sucrose and fructose elicit conditioned flavor preferences (CFP) that are also subject to marked differences across 8 inbred strains (Pinhas et al, 2012).…”
Section: Introductionmentioning
confidence: 83%
“…Whereas NTX moderately inhibited sucrose intake in BALB/c mice, it was ineffective in SWR mice (Dym et al, 2007). Conversely, NTX suppressed Intralipid intake in SWR, but not BALB/c mice (Dym et al, 2010). Although no studies have examined whether these two strains differ in opioid receptor binding, SWR mice display attenuated opioid-mediated responses to rewards as evaluated in morphine self-administration (Belknap et al, 1993) and conditioned place preference (Gieryk et al, 2010;Solecki et al, 2009).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation